Factors and Proposals for Improving the Efficiency of the Enforcement of Judicial Decisions in Ukraine - Zhukevych, Ihor; Dzikovskyi, Maksym; Kiriushyn, Dmytro; Koziar, Roman; Korniienko, Petro (NAJAHA, 2025)
This study aims to analyse the primary factors limiting the efficiency of judicial decision enforcement in Ukraine, identify the key determinants, and propose measures to enhance this process. The methodological foundation of the research used an analysis of regulatory legal acts and scientific literature. Academic sources were selected following the PRISMA method, which made it possible to attract the most relevant scientific literature (47 publications). The findings highlight that the failure to enforce judicial decisions in Ukraine is a multifaceted issue requiring further resolution. Specific challenges include economic constraints, inconsistencies in accessing data from various databases and registers, corruption-related matters, and the disproportion between state and private executors. Proposals for improvement include updating government programmes for the compensation of judicial debts and amending regulations on the sale of state property by lifting moratoriums on such sales. It is also proposed to increase the state’s share to 75% and restructure existing debts. Another potential measure involves increasing the number of private executors, granting them broader powers, and improving their access to state information. The methodology explicitly prioritised studies published in English to facilitate additional critique and analysis within the multinational research community, which tends to engage more actively with English-language publications. The conclusions emphasise that the current situation regarding the non-enforcement of judicial decisions requires further comprehensive reforms, particularly in the existing legislative framework. A promising area for further research is the analysis of foreign practices that can be applied to Ukrainian realities.